Introduction: networks in public administration - Bogason, Peter; Toonen, Theo A.J. (1998)
In the introductory article to the special issue on Comparing Networks, the editors discuss the meaning of the concept of networks in relation to other recent conceptual developments in public administration such as (neo)institutional and (neo)managerial analysis. They trace the broadly understood historical development of network analysis back to the late 1960s and early 1970s and highlight some important factors in its development up to the present-day demands placed on public administration by both globalization and decentralization. The result is organizational fragmentation. Network analysis makes it clear that people working in government and administration will have to learn to think of organization as an external, not internal activity. The prospect is that hierarchical control will be replaced by continuing processes of bargaining among interested parties within most fields of public administration. - Reproduced
Keywords: Public administration